2007
DOI: 10.1097/hjh.0b013e328244e3ac
|View full text |Cite
|
Sign up to set email alerts
|

Novel Compliance Index derived from digital volume pulse associated with risk factors and exercise capacity in patients undergoing treadmill exercise tests

Abstract: The Compliance Index was lower in patients with risk factors and was associated with poor exercise capacity. This index may be clinically useful for evaluating arterial stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 22 publications
0
19
0
2
Order By: Relevance
“…22) CI, derived from our photoplethysmography system, may be clinically useful for evaluating arterial stiffness of small to medium sized arteries. 14,15) We showed that both large and small arterial stiffening occurs in pre-DM patients in the current study. In Table III of our study, we found that the HOMA index, rather than fasting glucose and HbA 1C , was an independent determinant for CI after adjusting for important confounders.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…22) CI, derived from our photoplethysmography system, may be clinically useful for evaluating arterial stiffness of small to medium sized arteries. 14,15) We showed that both large and small arterial stiffening occurs in pre-DM patients in the current study. In Table III of our study, we found that the HOMA index, rather than fasting glucose and HbA 1C , was an independent determinant for CI after adjusting for important confounders.…”
Section: Discussionmentioning
confidence: 80%
“…31,32) We have previously showed that CI was lower in patients with risk factors and was associated with poor exercise capacity. 14) This index may be clinically useful for evaluating exercise capacity related to peripheral arterial stiffness.…”
Section: Possible Mechanisms Of Increased Arterial Stiffness In Pre-dmmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no differences in age and HR were found, the mean BP was different between groups (Table VI in the online-only Data Supplement). Two arterial stiffness indices, stiffness index and compliance index, 20,21 were measured. Obese and overweight subjects showed trends toward higher stiffness index than normal weight subjects ( Figure 6C).…”
Section: Arterial Stiffening and Lower Lox Levels In Obese Humansmentioning
confidence: 99%
“…58) Recently, the "Compliance index" derived from the digital volume pulse waveform was proposed; however, it showed lower values in patients with risk factors. 59) Although measurement of the digital volume pulse wave is easy, portable and useful for epidemiology studies, further investigation is needed for validation of various indices, such as its relationship with central aortic stiffness and predictability of cardiovascular risk.…”
Section: Digital Volume Pulse Wave Analysismentioning
confidence: 99%